Geomorfološka dediščina v Dolini Triglavskih jezer - Erhartič, Bojan (Geografija Slovenije, 2012)
This volume analyzes the relief of the Triglav Lakes Valley and evaluates the landforms in terms of nature protection. The central part of the study consists of two parts: a relief analysis and landform evaluation. Due to the fragmentation of relief forms, their different sizes and greater nature protection importance of areas with high density and diversity of forms, the relief is assessed according to 17 unified geomorphological units. The assessment employed the Swiss method, which comprises central (scientific) assessment criteria (rareness, representativeness, integrity and paleogeographical value) and is supplemented by additional criteria (ecological, aesthetic, cultural and economic value). The result of the relief analysis and the evaluation of geomorphological units is the cartographic, tabular, pictorial, and descriptive presentation of geomorphosites in the Triglav Lakes Valley. In addition, proposals are presented for conferring the status of natural value and protection.